Consumer price adjustment under the microscope: Germany in a period of low inflation - Johannes Hoffmann; Jeong-Ryeol Kurz-Kim (Deutsche Bundesbank, 2006)
We analyse the adjustment of retail and services prices in a period of low inflation, using a set of individual price data from the German Consumer Price Index which covers the years 1998 to 2003. We strong find evidence of time- and state-dependent price adjustment. Most importantly, the differences in ?unconditional? sectoral price flexibility are found to be linked to input price volatility.
Keywords: D43; E31; L11; 330; price rigidity; price flexibility; Consumer Price Index; Germany; Lebenshaltungsindex; Preisrigidität; Preis; Flexibilität; Inflation; Deutschland